Velocity thresholds for women`s soccer matches: Sex specificity dictates high-speed-running and sprinting thresholds - Female Athletes in Motion (FAiM) - Bradley, P. S.; Vescovi, J. D. (International Journal of Sports Physiology and Performance, 2015)
There is no methodological standardization of velocity thresholds for the quantification of distances covered in various locomotor activities for women`s soccer matches, especially for high-speed running and sprinting. Applying velocity thresholds used for motion analysis of men`s soccer has likely created skewed observations about high-intensity movement demands for the women`s game because these thresholds do not accurately reflect the capabilities of elite female players. Subsequently, a cohesive view of the locomotor characteristics of women`s soccer does not yet exist. The aim of this commentary is to provide suggestions for standardizing high-speed running and sprint velocity thresholds specific to women`s soccer. The authors also comment on using generic vs individualized thresholds, as well as age-related considerations, to establish velocity thresholds.